Contributors to Enhanced CO2 Electroreduction Activity and Stability in a Nanostructured Au Electrocatalyst. Issue 16 (28th July 2016) - Kim, Haeri; Jeon, Hyo Sang; Jee, Michael Shincheon; Nursanto, Eduardus Budi; Singh, Jitendra Pal; Chae, Keunhwa; Hwang, Yun Jeong; Min, Byoung Koun
Abstract: The formation of a nanostructure is a popular strategy for catalyst applications because it can generate new surfaces that can significantly improve the catalytic activity and durability of the catalysts. However, the increase in the surface area resulting from nanostructuring does not fully explain the substantial improvement in the catalytic properties of the CO2 electroreduction reaction, and the underlying mechanisms have not yet been fully understood. Here, based on a combination of extended X‐ray absorption fine structure analysis, X‐ray photoelectron spectroscopy, and Kelvin probe force microscopy, we observed a contracted Au−Au bond length and low work function with the nanostructured Au surface that had enhanced catalytic activity for electrochemical CO2 reduction. The results may improve the understanding of the enhanced stability of the nanostructured Au electrode based on the resistance of cation adhesion during the CO2 reduction reaction. Abstract : Enhanced CO2 reduction activity ! A combination of extended X‐ray absorption fine structure analysis and Kelvin probe force microscopy identified differences in the Au−Au bond length and work function values between nanostructured and flat Au. The deposition of cations from the electrolyte on the Au surface after CO2 reduction was investigated to determine its role in the degradation of the reduction performance.